MATLAB for electrical and computer engineering students and professionals, with Simulink - Priemer, Roland (Computing., 2013)
This book combines the teaching of MATLABʼ programming skills with the presentation and development of carefully selected electrical and computer engineering (ECE) fundamentals. This is what distinguishes it from many others: it is directed specifically to ECE concerns. Students will see, quite explicitly, how and why MATLAB is well suited to solve practical ECE problems. For ECE graduates of BS programs, MATLAB programming skills are an increasingly important component in the tool set for competing successfully in the job market. This requires that students start early in their academic studies to learn and apply MATLAB programming skills in their EE and CE curricula.